Optimal Molecular Methods in Detecting p190BCR-ABL Fusion Variants in Hematologic Malignancies: A Case Report and Review of the Literature - Rebecca J. Sonu; Brian A. Jonas; Denis M. Dwyre; Jeffrey P. Gregg; Hooman H. Rashidi (Case Reports in Hematology)
Patients with BCR-ABL1 positive hematologic malignancies and Philadelphia-like B-lymphoblastic leukemia (B-ALL) are potential candidates for targeted therapy with tyrosine kinase inhibitors (TKI). Before TKIs, patients with B-ALL had a much worse prognosis and current treatments with targeted TKI therapy have improved outcomes. Thus, the detection of BCR-ABL1 is crucial and a false negative BCR-ABL1 result may adversely affect patient care. We report a case of a 76-year-old male with a new diagnosis of B-ALL who was initially found to be BCR-ABL1 negative by quantitative polymerase chain reaction (PCR). A concurrent qualitative PCR was performed which detected a positive BCR-ABL1 result that was confirmed by a next generation sequencing (NGS) based assay and identified as the rare fusion variant e1a3 of p190BCR-ABL. Based on this result, the patient was placed on dasatinib as a targeted therapy. In the era of molecular diagnostic medicine and targeted therapy, it is essential to have an understanding of the limitations of molecular assays and to follow a comprehensive diagnostic approach in order to detect common abnormalities and rare variants. Incorporating NGS methods in an algorithmic manner into the standard diagnostic PCR-based approach for BCR-ABL1 will aid in minimizing false negative results.